A new genetic model of activity-induced Ras signaling dependent pre-synaptic plasticity in Drosophila - RAMASWAMI, MANI (My University, 2010)
Techniques to induce activity-dependent neuronal plasticity in vivo allow the underlying signaling pathways to be studied in their biological context. Here, we demonstrate activity-induced plasticity at neuromuscular synapses of Drosophila double mutant for comatose (an NSF mutant) and Kum (a SERCA mutant), and present an analysis of the underlying signaling pathways. comt; Kum (CK) double mutants exhibit increased locomotor activity under normal culture conditions, concomitant with a larger neuromuscular junction synapse and stably elevated evoked transmitter release. The observed enhancements of synaptic size and transmitter release in CK mutants are completely abrogated by: a) reduced activity of motor neurons; b) attenuation of the Ras/ERK signaling cascade; or c) inhibition of the transcription factors Fos and CREB. all of which restrict synaptic properties to near wild type levels. Together, these results document neural activity-dependent plasticity of motor synapses in CK animals that requires Ras/ERK signaling and normal transcriptional activity of Fos and CREB. Further, novel in vivo reporters of neuronal Ras activation and Fos transcription also confirm increased signaling through a Ras/AP-1 pathway in motor neurons of CK animals, consistent with results from our genetic experiments. Thus, this study: a) provides a robust system in which to study activity-induced synaptic plasticity in vivo; b) establishes a causal link between neural activity, Ras signaling, transcriptional regulation and pre-synaptic plasticity in glutamatergic motor neurons of Drosophila larvae; and c) presents novel, genetically encoded reporters for Ras and AP-1 dependent signaling pathways in Drosophila.
PUBLISHED
Keywords: Drosophila; Neuron; Plasticity; Ras; Genes & Society